Does physical trauma lead to an increase in the risk of new onset widespread pain?. Issue 3 (13th July 2005) - Wynne-Jones, G; Macfarlane, G J; Silman, A J; Jones, G T
Abstract : Objective: To determine the rate of new onset of widespread pain after a traumatic event (motor vehicle crash). Methods: A prospective cohort study of persons registered with an insurance company who had or had not experienced a motor vehicle crash. All participants were sent a questionnaire to assess pre-crash (or for the non-crash group, prior) psychosocial factors and widespread pain. Participants reporting pre-crash (prior) widespread pain were excluded. At six months, participants were sent a follow up questionnaire to ascertain new prevalent widespread pain. Results: 597 (51%) of participants returned a baseline questionnaire (465 crash and 132 non-crash). Among the cohort who had experienced a crash, the new onset rate of widespread pain six months later was low (8%), though in comparison with the non-crash group there was an increased risk (RR = 1.9 (95% CI, 0.8 to 4.8, adjusted for age and sex)); this was attenuated after adjustment for pre-crash (prior) psychological distress and somatic symptoms (RR = 1.4 (95% CI, 0.5 to 3.2)). Conclusions: The findings suggest that a motor vehicle crash (as an example of a physically traumatic event) is unlikely to have a major impact on the new onset of widespread pain. Any observed relation may, in part, be explained by psychological distress.